Serum paraoxonase-1 gene polymorphism and enzyme activity in patients with urolithiasis. (15th March 2016) - Atar, Arda; Gedikbasi, Asuman; Sonmezay, Erkan; Kiraz, Zeynep Kusku; Abbasoglu, Semra; Tasci, Ali Ihsan; Tugcu, Volkan
Abstract: Objectives Paraoxonase-1 (PON1) is a high-density lipoprotein-associated enzyme implicated in the pathogenesis of atherosclerosis by protecting lipoproteins against peroxidation. PON1 has two genetic polymorphisms both due to amino acid substitution, one involving glutamine and arginine at position 192 and the other leucine and methionine at position 55. Recent reports suggest that nephrolithiasis and atherosclerosis share a number of risk factors. Our study aimed to compare the effects of PON1 192, PON1 55 polymorphisms, and PON1 activity in patients with urolithiasis and controls.Materials and methods PON1's arylesterase/paraoxonase activities and phenotype were determined in 158 stone forming cases (Group 1) and 138 non-stone forming controls (Group 2). The PON1 192 and PON1 55 polymorphisms were studied by polymerase chain reaction/restriction fragment length polymorphism.Results Paraoxonase activity was significantly lower in Group 1 than Group 2 (112 ± 31.8 vs. 208 ± 53.1 IU/L) ( p  < 0.001). The PON1 L55M polymorphism was significantly higher in Group 1. The "M" allele coding for PON1 was higher in Group 1 ( p  < 0.001). PON1 192 RR homozygotes had significantly higher PON1 activity than QR and QQ genotypes among all the patients ( p  < 0.001).Conclusion The results of our study demonstrate that the PON1 55 gene "M" allele is associated with renal stone disease. Individuals possessing the "M" allele have a higher incidence of urolithiasis. The results of this study provide genetic evidence that the PON1 gene may play a role in stone formation. PON1 genotype determination may provide a tool to identify individuals who are at risk of urolithiasis.